Phytochemical Screening and Cytotoxicity Evaluation of Ethanolic Extract of Hypericum cordifolium (choisy) Leaves - Basyal, Deepak; Bhandari, Netra Lal (Journal of Nepal Chemical Society, 2019)
Hypericum cordifolium is a medicinal plant traditionally used for the treatment of the menstrual disorder, backache, dislocation of bone, fever, diarrhea and dysentery due to the presence of potential bioactive secondary metabolites. Ethanolic extract of dried leaf powder was prepared using the Soxhlet apparatus, followed by qualitative phytochemical screening with different reagents. In-vitro cytotoxicity assay was screened by using brine shrimp bioassay and LC50 was calculated by probit analysis. Alkaloids, glycosides, amino acids, and fixed oils were present at very minute level whereas saponin, phenol and flavonoids were present at significant level. Cytotoxicity assay of the leaf extract showed significant results (p